Pengaruh Pendidikan Kesehatan Tentang Bahaya Merokok Melalui Media Booklet Dan Poster Terhadap Pengetahuan Dan Sikap Siswa Smp N 2 Tasikmadu - Dharmastuti, Silvia Putri; , Yuli Kusumawati, S.K.M.M.ies. (Epid ); , Anisa Catur Wijayanti, S.K.M. M (Epid ) (2017)
The phenomenon of smoking is not only in adults but has penetrated into teenagers and even high school students. Not only senior high school students, but has expanded to junior high school students. One of efforts to stop smoking among adolescents is health education. The purpose of this study is to determine the effect of health education about the dangers of smoking through the booklets and posters media on knowledge and attitudes of students. Type of research is Quasi-experimental research with pre and post test. Population of this study are 946 students, the sample size is 164 respondents in each treatment group. Data analysis technique performed with Wilcoxon statistical test, test of validity, reliability, and normality. The results show there are differences of knowledge before and after health education about the dangers of smoking through the booklet media (p = 0,000) and poster media (p = 0,017). There are differences of attitude before and after health education about the dangers of smoking through the booklet media (p = 0,000) and there was no difference of attitudes before and after the poster media (p = 0,946). The results of the comparison test of health education with booklets and posters media showed difference in the effect of health education on the dangers of smoking to the media booklets and posters to knowledge (p = 0.000) and attitude (p = 0.000).